American Jewish Year Book 2017 The Annual Record of the North American Jewish Communities (American Jewish Year Book,, 2018)
The American Jewish Year Book, now in its 117th year, is the annual record of the North American Jewish communities and provides insight into their major trends. The first chapter of Part I is an examination of how American Jews fit into the US religious landscape, based on Pew Research Center studies. The second chapter examines intermarriage. Chapters on "The Domestic Arena" and "The International Arena" analyze the year's events as they affect American Jewish communal and political affairs. Three chapters analyze the demography and geography of the US, Canada, and world Jewish populations. Part II provides lists of Jewish institutions, including federations, community centers, social service agencies, national organizations, synagogues, Hillels, day schools, camps, museums, and Israeli consulates. The final chapters present national and local Jewish periodicals and broadcast media; academic resources, including Jewish Studies programs, books, journals, articles, websites, and research libraries; and lists of major events in the past year, Jewish honorees, and obituaries.